Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar IPA Fisika Peserta Didik Pada Konsep Usaha dan Energi di Kelas VII Madrasah Tsanawiyah Swasta Tomalou Tidore Kepulauan - Susi Ismail (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Influence of Discovery Learning Learning Model on Student Physics Science Learning Outcomes on Business and Energy Concepts in Class VII Madrasah Tsanawiyah Private Tomalou City, Tidore Islands. Supervised by Susi Ismail, M.Pd as supervisor I and Irawati Hi. Malan as supervisor II. Physics Education Study Program, Teacher Training and Educational Sciences College, Kie Raha Ternate. This study aims to determine the effect of the Discovery Learning learning model and student learning outcomes on the concept of business and energy for class VII Madrasah Tsanawiyah Swasta Toomalou City of Tidore Islands. This research is a quantitative research with experimental research type. The research subjects were students of class VII Mts S. Tomlaou Tikep, totaling 26 students. Experimental class students using the Discovery Learning learning model and students in the control class using the lecture method. The data were analyzed using the results of the normality analysis of the MinN-Gain experimental class 19.92 in the high category and MaxN-Gain 88.11, while the control class was MinN-Gain. 00 and MaxN-Gain 58.33 medium category. The results of this test show that between the experimental class and the control class.